Answer:
0.495
Step-by-step explanation:
Answer:
The correct option is 1/4^2
Step-by-step explanation:
The given expression is:
4^6 * 4^-8
According to the same base rule if the exponents have the same base then the exponents will be added.
If we look at the given expression both the values have the same base.
Therefore we will add the exponents of the value.
= 4^6+(-8)
= 4^6-8
= 4^-2
Now to change the negative exponent into positive we will take it to the denominator.
4^-2 = 1/4^2
Thus the correct option is A....
Answer: x = 23 and y = 13
Explanation:
let x and y be the two number.
Where:
(x + y)/2 = 18 => x + y = 18 x 2 = 36
and:
x - y = 10
Thus we get:
x + y = 36 (1)
x - y = 10 (2)
Add (1) and (2):
x + y + x - y = 36 + 10
2x = 46
x = 23
If x = 23
then x - y = 10
23 - y = 10
-y = -13
y = 13
The population growth will be modeled using exponential growth:
f(x)=a(b)^t
where:
a=initial value
b=growth rate
thus plugging in the values we get:
f(x)=1.3(1.04)^t
thus the population after 10 years will be:
f(x)=1.3(1.04)^10
f(x)=1.9243
thus the population in 10 years will be:
1.9243 million
Since you want to put this in simplest form ... the easiest way you can do it is
3 (100) + 97
So, step 1] 3(100)= 300
Step 2] 300 + 97 = 397
Answer : 397 over 100
(:
There's other ways too, but it'll take me all night to finish it